2016
DOI: 10.1159/000441709
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias in Patients with Decompensated Tinnitus: Prima Facie Evidence from Event-Related Potentials

Abstract: Tinnitus refers to the auditory perception of sound in the absence of external sound or electric stimuli. The influence of tinnitus on cognitive processing is at the cutting edge of ongoing tinnitus research. In this study, we adopted an objective indicator of attentional processing, i.e. the mismatch negativity (MMN), to assess the attentional bias in patients with decompensated tinnitus. Three kinds of pure tones, D1 (8,000 Hz), S (8,500 Hz) and D2 (9,000 Hz), were used to induce event-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The study reported that the 9000 Hz frequency induced a significant MMN in the group with tinnitus, and the amplitude of ERP between 90 and 150 ms was significantly higher in the group with tinnitus compared to the control group. The study proposed that persons with tinnitus may utilize automatic processing of acoustic stimuli and therefore may allocate more cognitive resources for such processing (Li et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported that the 9000 Hz frequency induced a significant MMN in the group with tinnitus, and the amplitude of ERP between 90 and 150 ms was significantly higher in the group with tinnitus compared to the control group. The study proposed that persons with tinnitus may utilize automatic processing of acoustic stimuli and therefore may allocate more cognitive resources for such processing (Li et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After baseline selection, the amplitude of labeled MMN peaks was calculated for six channels (F3, Fz, F4, FC3, FCz, and FC4) where MMN had the highest activity in the region of interest (ROI) channels extracting the frontal subcomponent of the MMN (Giard et al, 1990;Li et al, 2016). Also, for extracting the supratemporal subcomponent of the MMN, peaks were calculated for two channels, namely, M1 and M2 (Näätänen et al, 1978).…”
Section: Temporal Featuresmentioning
confidence: 99%
“…In a previous research based on cue-target paradigm, there had the interstimulus interval (ISI) between the cue and the target ( Chica et al, 2014 ), attention resources can be detached from cues to target stimuli, which affected the processing of target stimuli by individuals. However, the attention resources occupied by tinnitus were difficult to separate from the tinnitus signal ( Li et al, 2016 ), thus tinnitus was hard to relate to target stimulation and cannot act as the spatial cue in visual processing.…”
Section: Discussionmentioning
confidence: 99%
“…The difference of the CAEP waveform for each set of speech stimulus was used to measure the MMN response, which was obtained by subtracting the averaged responses of the deviant stimuli from the averaged responses of the same stimuli presented as the standard. MMN was defined as a component having the largest negativity occurring between 100-250 ms at electrode positions Fz or Cz (Duncan et al 2009;Li et al 2016). The appearance of MMN was confirmed when it had more negative amplitudes at the fronto-central electrode site (Fz and Cz) in comparison with the parietal site (Pz).…”
Section: Cortical Auditory Evoked Potential (Caep) Waveforms Measuremmentioning
confidence: 99%